Pengaruh Parkir pada Badan Jalan terhadap Kinerja Ruas Jalan Indrakila Kota Balikpapan - Nggolib Fuadana; Maslina Maslina (Universitas Batanghari Jambi, 2026)
On-street parking problems along roads can have a significant impact on traffic performance, especially in terms of congestion and road capacity. Vehicles parked on the road cause side obstacles, reduce traffic flow, and worsen road conditions. This study aims to evaluate the impact of on-street parking on traffic performance on Jalan Indrakila, Balikpapan City. The research method used is a quantitative approach with a case study. Primary data was obtained through field surveys that included measurements of traffic volume, lateral obstructions, and vehicle travel time. Secondary data in the form of literature and supporting documents was used to analyze road capacity and calculate the level of service. The results show that on-street parking on Jalan Indrakila causes a significant decrease in road capacity, with a degree of saturation reaching 0.8 in conditions with parking and 0.5 in conditions without parking. High side obstructions in this area also contribute to the decline in road performance. In conclusion, better parking management and careful planning are essential to reduce negative impacts on traffic and support smooth mobility and local economic growth.